Human CD5+ Innate Lymphoid Cells Are Functionally Immature and Their Development from CD34+ Progenitor Cells Is Regulated by Id2 - Nagasawa, Maho; Germar, Kristine; Blom, Bianca; Spits, Hergen (Frontiers in Immunology, 2017)
Innate lymphoid cells (ILCs) have emerged as a key cell type involved in surveillance and maintenance of mucosal tissues. Mouse ILCs rely on the transcriptional regulator Inhibitor of DNA binding protein 2 (Id2) for their development. Here we show that Id2 also drives development of human ILC because forced expression of Id2 in human thymic progenitors blocked T cell commitment, upregulated CD161 and promyelocytic leukemia zinc finger (PLZF), and maintained CD127 expression, markers that are characteristic for human ILCs. Surprisingly CD5 was also expressed on these in vitro generated ILCs. This was not an in vitro artifact because CD5 was also found on ex vivo isolated ILCs from thymus and from umbilical cord blood (UCB). CD5 was also expressed on small proportions of ILC2 and ILC3. CD5+ ILCs were functionally immature, but could further differentiate into mature CD5 cytokine-secreting ILCs. Our data show that Id2 governs human ILC development from thymic progenitor cells towards immature CD5+ ILCs.